Analisis Penentuan Tarif Kamar Hotel dengan Metode Activity Based Costing Hotel Resty Menara Pekanbaru - Laia, Andi Swerman; Br. Naibaho, Ester Agustina Indah; Br. Simbolon, Lasmia Rotua (CV. Kalimasada Group, 2024)
This research aims to analyze and optimize room rates at the Resty Tower Pekanbaru Hotel using the Activity Based Costing (ABC) method. This research combines qualitative and quantitative approaches in data collection, including direct observation, interviews and document analysis. Qualitative data provides an in-depth look at the hotel's internal procedures, while quantitative data covers operational costs specific to each hotel activity. The analysis results show that by using more efficient operational costs based on ABC, room rates can be reduced significantly from current rates.